Gasoline direct injection engines – A review of latest technologies and trends. Part 1: Spray breakup process. (1st April 2020) - Duronio, Francesco; De Vita, Angelo; Allocca, Luigi; Anatone, Michele
Highlights: Gasoline Direct Injection engines review. Spray breakup process. Experimental and numerical gasoline spray characterization. Spray-wall impact. Abstract: The ever more stringent vehicle emissions rules are leading gasoline engine research and development toward the use of direct injection systems. This technology is already present in commercial vehicles, but there are still many aspects that can be improved and need a deeper investigation. For this reason, it was considered important to provide a review of the latest research topics, sorting them as if we are following the ideal life of a fuel droplet, beginning from the injection and ending after the combustion reaction, making available to researchers a tool to understand the state of the art of gasoline direct injection's research and technologies. Spray breakup is the first and crucial process that occurs when the fuel is injected within the combustion chamber, and it is treated extensively and in detail in the literature. In this work, a broad analysis of new mathematical models and experimental imaging techniques, used to study spray breakup and the subsequent impact on the engine surfaces, is reported and commented on. The studies aim at a broader understanding of the phenomena, a better characterisation of the jet, and the final optimisation of the engine design. In a subsequent work (Part 2), a research review on the mixture formation process, combustion and emission characterisation will be addressed.